Algorithms for tight spans and tropical linear spaces. (March 2019) - Hampe, Simon; Joswig, Michael; Schröter, Benjamin
Abstract: We describe a new method for computing tropical linear spaces and more general duals of polyhedral subdivisions. This is based on an algorithm of Ganter for finite closure systems.